Mechanical and seepage characteristics of mining unloading sandstone under action of confined water - Peisen ZHANG; Hongwei WANG; Shouzhen YANG; Daqiang XU; Yeqiang LIU; Chao LIU; Jiaxin FANG; Zhaoqiang JU (Meitan kexue jishu)
Abstract：With the continuous deepening of coal mining to the deep, the threat of high confined water to coal mining face increases significantly, which is easy to induce water inrush disaster. Based on this, Rock Top multi-field coupling tester is used to simulate the mining stress under confined water environment, and sandstone unloading test is carried out. The stress path of axial pressure (stress concentration) and confining pressure reduction (excavation unloading) is adopted to explore the mechanical and seepage characteristics of sandstone under different initial unloading levels and different osmotic pressure differences. The mechanical and seepage characteristics of mining unloading sandstone under the action of confined water are obtained. The results show that: The stress-strain curve of sandstone appears “shunt” phenomenon due to different initial unloading levels, and unloading will accelerate the development process of internal cracks in rock samples. The peak average effective stress of rock sample increases with the increase of osmotic pressure difference and unloading level. The peak radial strain increases with the increase of unloading level. With the increase of the initial unloading level, the peak circumferential strain shows a downward trend as a whole. The effective unloading modulus of the internal structure of rock mass is defined. The higher the initial unloading level is, the smaller the osmotic pressure difference is, the lower the effective unloading modulus of the internal structure of rock mass is, and the worse the deformation resistance of the internal structure of rock sample. The typical permeability curve of sandstone shows the law of “decrease−increase−decrease−stability.” The permeability curve of sandstone in low permeability environment shows obvious “peak” stage after rock failure, and the “peak” stage in high permeability environment is relatively not obvious. The total volume curve of the seepage channel has a good correspondence with the permeability curve; the flow velocity curve of the seepage field conforms to the change rule of “drop−increase−flat”. The flow velocity is large under high osmotic pressure difference, and the flow velocity is small and reverse seepage occurs under low osmotic pressure difference.